KNOWLEDGE, PERCEPTION AND ATTITUDE OF NURSING STUDENTS AT SUEZ CANAL UNIVERSITY, EGYPT TOWARD COVID-19 PATIENTS - El-Hossany, Wafaa Abd El-Azeem; Ahmed, Mahitab Mohamed; Ali, Nahed M. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Background: Covid-19 infection has spread globally, posing a serious threat to many countries, especially those in developing countries. Due to a lack of capabilities and preparations, some governments decided to train medical and nursing internship students to raise awareness and encourage healthy actions in the face of the pandemic. The aim of this study was to evaluate nursing students’ knowledge, perceptions, and attitudes toward covid-19 patients. Methods: A descriptive cross-sectional study was conducted on Nursing students of the 4th academic year and internship (N=302) at Suez Canal University in Egypt. Data was collected through a validated online self-administrated questionnaire. Results: The total mean score of the studied students’ knowledge (24.24± (4.17 was fair while they had positive attitude (67.55± 6.87) and good perception (69.28± 7.69). There was a statistically significant correlation between students’ knowledge and perception (r=.114, p=.048) and between their attitude and perception (r=.284, p=.000). Conclusions: The average score of nursing students’ awareness of the COVID-19 pandemic was fair, according to the study. They did, however, have a positive attitude and perception. Most of them were concerned about infecting family members, losing their jobs if they were infected, and making medical mistakes when working with COVID-19 patients. Recommendation: On facing the second wave of COVID-19, Nursing students may need the following: Training courses to strengthen their understanding, awareness, and attitude toward pandemic preparedness. Governmental/ institution guidelines to ensure that they are protected from legal liability.